2015
DOI: 10.1111/gtc.12315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6‐meals‐a‐day feeding and 6‐meals‐a‐day feeding combined with adrenalectomy on daily gene expression rhythms in rat epididymal white adipose tissue

Abstract: The master clock in the hypothalamic suprachiasmatic nucleus (SCN) is assumed to synchronize the tissue-specific rhythms of the peripheral clocks with the environmental day/night changes via neural, humoral and/or behavioral connections. The feeding rhythm is considered an important Zeitgeber for peripheral clocks, as daytime feeding reverses (clock) gene rhythms in the periphery, but not in the SCN. In this study, we investigated the necessity of a daily feeding rhythm for maintaining gene expression rhythms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 58 publications
(150 reference statements)
8
23
0
Order By: Relevance
“…In the present study we showed that the daily rhythm of clock gene expression in the liver is still intact under 6-meals-a-day feeding conditions, after adrenalectomy, after total hepatic denervation or after total hepatic denervation with adrenalectomy or 6-meals-a-day feeding schedule. These results are similar to previous findings in liver (Cailotto et al 2005;Oishi et al 2005;Pezuk et al 2012;Sujino et al 2012), epididymal white adipose tissue (eWAT) (Su et al 2014(Su et al , 2015, kidney (Pezuk et al 2012;Sujino et al 2012), salivary gland (Pezuk et al 2012) and lung (Pezuk et al 2012). Together these findings demonstrate that feeding rhythm, adrenal hormones (in particular corticosterone) and neuronal inputs are not indispensable for synchronized daily clock gene rhythms.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study we showed that the daily rhythm of clock gene expression in the liver is still intact under 6-meals-a-day feeding conditions, after adrenalectomy, after total hepatic denervation or after total hepatic denervation with adrenalectomy or 6-meals-a-day feeding schedule. These results are similar to previous findings in liver (Cailotto et al 2005;Oishi et al 2005;Pezuk et al 2012;Sujino et al 2012), epididymal white adipose tissue (eWAT) (Su et al 2014(Su et al , 2015, kidney (Pezuk et al 2012;Sujino et al 2012), salivary gland (Pezuk et al 2012) and lung (Pezuk et al 2012). Together these findings demonstrate that feeding rhythm, adrenal hormones (in particular corticosterone) and neuronal inputs are not indispensable for synchronized daily clock gene rhythms.…”
Section: Discussionsupporting
confidence: 91%
“…We found that the daily rhythm of clock gene expression was lost after simultaneous disruption of the adrenal hormone and feeding rhythms, a result very much similar to what Ikeda et al (Ikeda et al 2014) found in mouse liver and kidney and what Su et al found in white adipose tissue (Su et al 2015). In their mice study Ikeda et al (Ikeda et al 2014) showed that 6M þ ADX treatment affected clock gene rhythms in the periphery without affecting the SCN clock.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…factors that do not lose their daily rhythmicity in the 6M condition, such as corticosterone or melatonin (Su et al 2016b). Interestingly, Shp lost its rhythm in the 6M condition suggesting that Shp mRNA expression is more strongly driven by food intake than by the hepatic molecular clock.…”
Section: Discussionmentioning
confidence: 99%